2008
DOI: 10.1002/cjoc.200890106
|View full text |Cite
|
Sign up to set email alerts
|

Extra Copper‐mediated Enhancement of the DNA Cleavage Activity Supported with Wild‐type Cu, Zn Superoxide Dismutase

Abstract: It is well known that the primary function of wild type Cu, Zn superoxide dismutase (holo SOD) is to catalyze the conversion of the superoxide anion to H 2 O 2 and O 2 as an antioxidant enzyme. However, the aberrant copper-mediated oxidation chemistry in the enzyme (including its mutation forms) that damages nucleic acids, proteins including itself and cell membrane has attracted extensive attention in the past decade. The present study examined the hydrogen peroxide-dependent DNA cleavage activity supported w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A series of catalysts with different acidity and basicity were prepared and fully characterized in this investigation. The results revealed that the introduction of sulfur significantly affected the acidity and alkalinity of the oxide surface [28][29][30]. However, different from the same reaction catalyzed by fluorinated MgAlO (MgAlO-F) under high pressure [31], the MgAl bilayer oxide modified by sulfate could promote the reaction more efficiently and can operate with mild conditions.…”
Section: Introductionmentioning
confidence: 95%
“…A series of catalysts with different acidity and basicity were prepared and fully characterized in this investigation. The results revealed that the introduction of sulfur significantly affected the acidity and alkalinity of the oxide surface [28][29][30]. However, different from the same reaction catalyzed by fluorinated MgAlO (MgAlO-F) under high pressure [31], the MgAl bilayer oxide modified by sulfate could promote the reaction more efficiently and can operate with mild conditions.…”
Section: Introductionmentioning
confidence: 95%